1981
DOI: 10.1021/jm00135a019
|View full text |Cite
|
Sign up to set email alerts
|

4-Aryl-4-aminocyclohexanones and their derivatives, a novel class of analgesics. 3. m-Hydroxyphenyl derivatives

Abstract: Derivatives of 4-aryl-4-(dimethylamino)cyclohexan-1-ones substituted by m-hydroxy groups were obtained by using as a key reaction the displacement of cyanide from the alpha-aminonitrile of 1,4-cyclohexanedione ketal, with the THP ether of m-hydroxyphenylmagnesium bromide. A number of the products show narcotic antagonist activity. Amino alcohols obtained on reaction of the free ketones with phenethyl Grignard reagents are potent analgetics, though devoid of antagonist activity. Systematic variation of the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was originally stated that BDPC/bromadol had 10,000 times the analgesic potency of morphine in animal studies [ 34 ] although a more recent study, comparing analgesic potency using a standard mouse hot plate assay where BDPC/bromadol was introduced by intraperitoneal injection, suggests that its analgesic potency may be lower, at around 500 times that of morphine and 2.9 times that of fentanyl [ 36 ]. BDPC/bromadol was the lead compound for a further series of 4-amino-4-arylcyclohexanone analogues and their derivatives prepared by the Upjohn team to provide structure activity relationship data [ 16 , 37 , 38 ]. None had analgesic properties greater than BDPC/bromadol, although a trans -chlorinated analogue showed similar potency as did an analogue where the phenethyl moiety was replaced with a cyclohex-3-ene moiety [ 37 ].…”
Section: Licit Drug Development: Evolution Of the N mentioning
confidence: 99%
“…It was originally stated that BDPC/bromadol had 10,000 times the analgesic potency of morphine in animal studies [ 34 ] although a more recent study, comparing analgesic potency using a standard mouse hot plate assay where BDPC/bromadol was introduced by intraperitoneal injection, suggests that its analgesic potency may be lower, at around 500 times that of morphine and 2.9 times that of fentanyl [ 36 ]. BDPC/bromadol was the lead compound for a further series of 4-amino-4-arylcyclohexanone analogues and their derivatives prepared by the Upjohn team to provide structure activity relationship data [ 16 , 37 , 38 ]. None had analgesic properties greater than BDPC/bromadol, although a trans -chlorinated analogue showed similar potency as did an analogue where the phenethyl moiety was replaced with a cyclohex-3-ene moiety [ 37 ].…”
Section: Licit Drug Development: Evolution Of the N mentioning
confidence: 99%
“…7,8 As a starting point it was clear that, due to its size, compound 1 would lack key interactions within the binding pocket of both the NOP and MOP receptors and therefore would have only minimal receptor binding affinities (K i (NOP) = 1.5 μM; K i (MOP) = 1.7 μM). It was our strategy to utilize 1 as a core and its ketone moiety for functionalization.…”
mentioning
confidence: 99%
“…This endeavor started with a literature-to-lead approach based on cyclohexanone 1 , which has previously been reported by Lednicer et al as representing a novel class of analgesics. , As a starting point it was clear that, due to its size, compound 1 would lack key interactions within the binding pocket of both the NOP and MOP receptors and therefore would have only minimal receptor binding affinities ( K i (NOP) = 1.5 μM; K i (MOP) = 1.7 μM). It was our strategy to utilize 1 as a core and its ketone moiety for functionalization.…”
mentioning
confidence: 99%
“…Cebranopadol ( 6 ) (Figure ) was designed as a combined NOP and multitargeted opioid agonist ligand based on preclinical research findings that suggested the coactivation of MOP and NOP receptors may potentiate pain relief, but not adverse-effects, thereby improving tolerability relative to clinically used strong opioid analgesics. , The discovery process employed a literature-to-lead campaign that was validated incrementally by receptor binding pocket docking. , The initial drug design concept was inspired by a series of literature disclosures made in the 1980s by Von Voigtlander that highlighted 4-amino-4-arylcyclohexanones (e.g., 61 ) (Figure ) as a novel class of analgesics. A substantial SAR study was undertaken by Schunk et al, which saw the first lead structure ( 62 ) (Figure ) docked into the active site of the NOP receptor .…”
Section: Multitargeted Opioid Analgesicsmentioning
confidence: 99%